Pengaruh Angka Harapan Hidup, Rata-rata Lama Sekolah dan Paritas Daya Beli Terhadap PDRB di Kalimantan Selatan - Auliana, Liqa; Sa’roni, Chairul (PPJP Universitas Lambung Mangkurat, 2023)
This study shows the effect of life expectancy, average length of schooling, and purchasing power parity on GRDP in South Kalimantan. This study uses secondary data obtained from the Central Statistics Agency in 2011-2020, with time series analysis data; the results of the study state: life expectancy has a negative and insignificant effect on GRDP in South Kalimantan; the average length of schooling has a positive and significant impact on GRDP in South Kalimantan; Purchasing power parity has a positive and significant effect on GRDP in South Kalimantan; The value of the determinant coefficient (R2) is 0.974301 with the intention that GRDP is influenced by three variables, namely life expectancy, average length of schooling and purchasing power parity 97% and the rest is influenced by other factors 3%.